2016
DOI: 10.1080/13607863.2016.1268091
|View full text |Cite
|
Sign up to set email alerts
|

A relationship-focused investigation of spousal psychological adjustment to dual-sensory loss

Abstract: The current study's findings provide support for a relationship-focused perspective of spousal psychological adjustment in the context of DSL. Further, couples' sensory loss-related communication is presented as a potential intervention target to enhance spouse perceived support and psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Research on caregiving dyads generally focuses on spousal relationship quality and according to Lehane et al (2018a) research and consistent with previous studies (Lehane et al, 2017a,b;Hofsoe et al, 2018) spousal relationships in a DSI context may experience significant strain. Using the relationship intimacy model, this study measured relationship satisfaction, perceived support and psychological well-being in 45 spouses of older adults with DSI, demonstrating that interpersonal communication and perceived support were associated with improved psychological well-being.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Research on caregiving dyads generally focuses on spousal relationship quality and according to Lehane et al (2018a) research and consistent with previous studies (Lehane et al, 2017a,b;Hofsoe et al, 2018) spousal relationships in a DSI context may experience significant strain. Using the relationship intimacy model, this study measured relationship satisfaction, perceived support and psychological well-being in 45 spouses of older adults with DSI, demonstrating that interpersonal communication and perceived support were associated with improved psychological well-being.…”
Section: Introductionsupporting
confidence: 65%
“…Irrespective of the nature of the care-giving relationship, the adoption of the care-giving role in a potentially already strained relationship will impose additional interpersonal tensions and suggests that understanding DSI as a collective experience, as suggested by Lehane et al (2018a) has the potential to offer more targeted support strategies for the family carer and improve quality of life for both. Given that family carers assume the bulk of care-giving responsibilities, this lends weight to the current focus of our study where the effects of DSI are considered a shared experience.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent articles have described the experiences of being the partner of someone who has dual sensory loss (i.e., concurrent hearing and vision loss) (Lehane et al, 2017a(Lehane et al, ,b, 2018. These studies have focused mainly on members of the aging population and the challenges they face due to the changed way of communication and the effects on their wellbeing or sexuality.…”
Section: Family Lifementioning
confidence: 99%
“…Facing the progressive loss of hearing and/or vision has been reported as a distressing and life-altering experience not only for OAWSLs but also for their spouses (Lehane, Dammeyer, & Elsass, 2017). Indeed, it can be expected that each spouse’s ability to adjust to the sensory loss may depend on the support that they receive from one another, or the lack thereof (Lehane, Elsass, Hovaldt, & Dammeyer, 2016). Previous research on couples’ adjustment to sensory loss has reported mixed results regarding the link between supportive behaviors from one’s spouse and mental health outcomes.…”
Section: Spouse Support and Its Association With Couples’ Mental Healthmentioning
confidence: 99%